Study and Implementation of Lean Manufacturing in a Garment Manufacturing Company: Bangladesh Perspective - Ripon Kumar Chakrabortty; Sanjoy Kumar Paul (Journal of Optimization in Industrial Engineering, 2011)
Lean manufacturing is a systematic approach to identifying and eliminating wastes (non-value added activities) through continuous improvement by conveying the product at the pull of the customer in pursuit of production. In a more basic term, more value with less work. Since lean manufacturing eliminates many of the problems associated with poor production scheduling and line balancing, lean manufacturing is particularly appropriate for companies that do not have ERP systems in place or do not have strong material requirements planning (MRP), production scheduling, or production allocation systems in place. This is particularly significant in Bangladesh, where many private Bangladeshi garment manufacturing companies are operating significantly below their potential capacity, or experiencing a high level of late-deliveries, due to problems with their current production scheduling and production management systems. Considering all